The NIN transcription factor coordinates CEP and CLE signaling peptides that regulate nodulation antagonistically - Carole Laffont; Ariel Ivanovici; Pierre Gautrat; Mathias Brault; Michael Anthony Djordjevic; Florian Frugier (Nature Communications)
Abstract Legumes tightly regulate nodule number to balance the cost of supporting symbiotic rhizobia with the benefits of nitrogen fixation. C-terminally Encoded Peptides (CEPs) and CLAVATA3-like (CLE) peptides positively and negatively regulate nodulation, respectively, through independent systemic pathways, but how these regulations are coordinated remains unknown. Here, we show that rhizobia, Nod Factors, and cytokinins induce a symbiosis-specific CEP gene, MtCEP7, which positively regulates rhizobial infection. Via grafting and split root studies, we reveal that MtCEP7 increases nodule number systemically through the MtCRA2 receptor. MtCEP7 and MtCLE13 expression in rhizobia-inoculated roots rely on the MtCRE1 cytokinin receptor and on the MtNIN transcription factor. MtNIN binds and transactivates Mt CEP7 and MtCLE13, and a NIN Binding Site (NBS) identified within the proximal MtCEP7 promoter is required for its symbiotic activation. Overall, these results demonstrate that a cytokinin-MtCRE1-MtNIN regulatory module coordinates the expression of two antagonistic, symbiosis-related, peptide hormones from different families to fine-tune nodule number.